Links Between Inflammatory Bowel Disease and Chronic Obstructive Pulmonary Disease - Raftery, April L.; Tsantikos, Evelyn; Harris, Nicola L.; Hibbs, Margaret L. (Frontiers in Immunology, 2020)
Keywords: Inflammatory bowel disease, Crohn's disease, chronic obstructive pulmonary disease, microbial dysbiosis, gut-lung axis.Inflammatory bowel disease (IBD) and chronic obstructive pulmonary disease (COPD) are chronic inflammatory diseases of the gastrointestinal and respiratory tracts, respectively. These mucosal tissues bear commonalities in embryology, structure and physiology. Inherent similarities in immune responses at the two sites, as well as overlapping environmental risk factors, help to explain the increase in prevalence of IBD amongst COPD patients. Over the past decade, a tremendous amount of research has been conducted to define the microbiological makeup of the intestine, known as the intestinal microbiota, and determine its contribution to health and disease. Intestinal microbial dysbiosis is now known to be associated with IBD where it impacts upon intestinal epithelial barrier integrity and leads to augmented immune responses and the perpetuation of chronic inflammation. While much less is known about the lung microbiota, like the intestine, it has its own distinct, diverse microflora, with dysbiosis being reported in respiratory disease settings such as COPD. Recent research has begun to delineate the interaction or crosstalk between the lung and the intestine and how this may influence, or be influenced by, the microbiota. It is now known that microbial products and metabolites can be transferred from the intestine to the lung via the bloodstream, providing a mechanism for communication. While recent studies indicate that intestinal microbiota can influence respiratory health, intestinal dysbiosis in COPD has not yet been described although it is anticipated since factors that lead to dysbiosis are similarly associated with COPD. This review will focus on the gut-lung axis in the context of IBD and COPD, highlighting the role of environmental and genetic factors and the impact of microbial dysbiosis on chronic inflammation in the intestinal tract and lung.